Constraints And Challenges Of Halal Product Guarantee In The Syariate Area - Fithri Mawaddah (STAI Al-Washliyah Banda Aceh, 2020)
Halal food plays a very big role in improving the image of Aceh Province as the only region that applies Islamic law in Indonesia. If viewed from the context of uncertainty, the implementation of halal food products in Aceh has not gone along with the implementation of the Sharia. Ironically, the guarantee of halal products as a legal umbrella for halal food products has only been legalized after 15 years of the Islamic Sharia in Aceh, precisely on December 19, 2016, Aceh has an important regulation governing halal products. This qualitative descriptive writing aims to explore and answer whether the obstacles and challenges in the implementation of guarantees for halal products, especially halal food in Banda Aceh City as the Capital City of the Shari'a. Data collection uses interviews, observation, and documentation techniques. Interviews were conducted with Banda Aceh City stakeholders and the LPPOM MPU Aceh. The results of the study show that there are several obstacles in halal certification as a form of halal product guarantee, namely: budget constraints, the absence of sanctions for entrepreneurs who do not have halal certificates and halal certificates have not had a significant impact on business actors, limited resources or auditors in the industry. LPPOM MPU, as well as a relatively long time required by business actors in completing administrative requirements. The challenge is the existence of halal stigma formed in the community and the commitment of the auditors. Therefore, stakeholders' seriousness is needed starting from regulation to oversee the implementation of halal food products that will have implications for the tasks, principal, and functions together and be able to open the mindset of halal product guarantees that exist in the community of Banda Aceh City.